The Citizenship Project Part II: Impact of a Citizenship Intervention on Clinical and Community Outcomes for Persons with Mental Illness and Criminal Justice Involvement. Issue 1 (7th August 2012) - Clayton, Ashley; O'Connell, Maria J.; Bellamy, Chyrell; Benedict, Patricia; Rowe, Michael
Abstract: This study assessed the effectiveness of an intervention based on a theoretical framework of citizenship on reducing psychiatric symptoms, alcohol use, and drug use, and increasing quality of life for persons with serious mental illness (SMI) and criminal justice involvement. One‐hundred fourteen adults with SMI and a history of criminal justice involvement participated in a 2 × 3 longitudinal randomized controlled trial of a four‐month citizenship intervention versus usual services. Linear mixed model analyses were used to assess the intervention's impact on quality of life, symptoms, and substance use. After controlling for baseline covariates, participants in the experimental condition reported significantly increased quality of life, greater satisfaction with and amount of activity, higher satisfaction with work, and reduced alcohol and drug use over time. However, individuals in the experimental condition also reported increased anxiety/depression and agitation at 6 months (but not 12 months) and significantly increased negative symptoms at 12 months. Findings suggest that community‐oriented, citizenship interventions for persons with SMI and criminal justice histories may facilitate improved clinical and community outcomes in some domains, but some negative clinical findings suggest the need for post‐intervention support for intervention participants. Implications for practice and future research are discussed.